Motivated belief updating and rationalization of information - Christoph Drobner; Sebastian J. Goerg (ZBW - Leibniz Information Centre for Economics, 2021)
We study belief updating about relative performance in an ego-relevant task. Manipulating beliefs about the ego-relevance of the task, we show that subjects update their beliefs about relative performance more optimistically as direct belief utility increases. This finding provides clean evidence for the optimistic belief updating hypothesis and supports theoretical models with direct belief utility. Moreover, we document that subjects ex-post rationalize information by discounting their beliefs about the ego-relevance of the task as the number of bad signals increases. Taken together, these findings suggest that subjects use two alternative strategies to protect their ego despite the presence of objective information.
Keywords: C91; D83; D84; 330; Motivated beliefs; Optimistic belief updating; Direct belief utility; Bayes' rule; Ex-post rationalization